KERIPIK TERONG SEBAGAI ALTERNATIF OLAHAN HASIL PERTANIAN DUSUN PONDOK, SENDANG, JAMBON, PONOROGO - Moh Faizin; Dwi Agung Wahyu Saputra (STKIP Persada Khatulistiwa Sintang, 2020)
Abstract: The people of Sendang Village, Jambon Subdistrict, Ponorogo Regency, especially Pondok Country, were mostly farmers. Some farmers in Pondok Country grew vegetables, especially eggplant. In general, eggplant was only intercropping plant or crop interlude in some part of the land they plant. So far, the farmers had suffered losses because the eggplants’ prices tended to be unstable. Therefore, this community service activity was carried out to empower the people of Pondok Country in social entrepreneurship activities to solve the problems that existed in the community environment. The community service team provided training to the community by making alternative processed products in the form of eggplant chips. This activity consisted of three stages, namely preparation, implementation and evaluation. At the implementation stage, the activities carried out in the form of training in making eggplant chips. The training was held in one of the houses of the residents. The result of this activity was the formation of social entrepreneurship growing in the community environment with products in the form of processed eggplant chips that can increase the community income. The processing of eggplants into chips could also minimize the farmers' losses because the chips were not stale easily and the prices became stable.